La virtud de lo virtual en la universidad de la sociedad del conocimiento (2010)
This society of knowledge and information that is supported by the widespread use of ICT brings changes that reach all areas of human actions. Its effects are manifested more particularly in educational activities ranging from teaching and learning methods, to the facilities and means used toward this purpose, as well as the organizational structure of the schools and the culture to which they belong. Teaching in higher education is going through a revolution, because the processes of teaching and learning, which for centuries had been entirely focused on traditional class patterns, are demanding today an interdisciplinary and transdisciplinary work in order to foster knowledge, research and inquisitiveness. This is not only in the classroom with rigid schemes, but in an emerging knowledge society and computer world, where virtual learning becomes a basic need for students and teachers at any level of schooling anywhere in the world.